Absensi Regionalisme di Asia Timur dari Perspektif Jepang - Arief, Audrey Diva Azzahra; Kalisang, Rahel Jechire (Jurnal Sentris, 2024)
The absence of East Asian regionalism has become a problem along with the increasing political tensions and the competition for military power from the member countries of the region. However, the bright spot for the creation of regionalism is not increasingly emerging and instead Japan, China and Korea choose their respective allies in the uncertainty of this international political contestation. History proves the truth today, that disputing countries will not easily cooperate in the same forum unless assisted by a third party. In this case, ASEAN is a liaison through ASEAN+3 and from Japan's perspective this situation is good. Cooperation between Japan and China, Japan and Korea and a mixture of the three often occurs bilaterally or non-bilaterally through ASEAN. Following the flow of the existing problems, a research question was formulated, "From a Japan perspective, why didn't regionalism have been created in the East Asia region even though a regionalization process had been established?" To help formulate answers in this article the author uses qualitative methods and critical security studies theory. From a Japan perspective, the absence of East Asian regionalism occurs because of the long history experienced by powerful countries in the region. Regionalism is increasingly suppressed in its development because the dynamics of the region are tenuous, tense and tend to experience fluctuations due to social, economic and military struggles, especially nuclear weapons. Keywords: Regionalism; East Asia; Japan; ASEAN+3; History Absensi regionalisme Asia Timur menjadi masalah seiring dengan meningkatnya ketegangan politik dan perlombaan adu kekuatan militer dari negara-negara anggota kawasannya. Hal tersebut menunjukkan kegagalan kohesi kawasan. Titik terang untuk pembuatan regionalisme ini tidak kian muncul dan malahan Jepang, Cina dan Korea Utara memilih sekutunya masing-masing dalam ketidakpastian kontestasi politik internasional ini. Sejarah membuktikan kebenarannya hari ini, bahwa negara yang pernah berselisih tidak akan secara mudah bekerja sama dalam satu wadah mereka sendiri kecuali diikuti bantuan oleh pihak ketiga. Keterlibatan pihak ketiga seperti ASEAN dalam ASEAN+3 membuat kohesi antar negara ini semakin hilang, akibat mereka tidak terkoneksi secara langsung dan independen. ASEAN yang menjadi penghubung melalui ASEAN+3 dianggap baik dari perspektif Jepang. Mengikuti alur permasalahan yang ada, dirumuskan sebuah pertanyaan penelitian, “Dari perspektif Jepang, mengapa tidak tercipta regionalisme di kawasan Asia Timur walaupun telah terjalin proses regionalisasi?.” Untuk membantu perumusan jawaban, dalam artikel ini penulis menggunakan metode kualitatif dan teori konstruktivisme serta konsep dilema keamanan. Dari perspektif Jepang, absensi regionalisme Asia Timur terjadi karena sejarah panjang yang dilalui oleh negara-negara kuat di kawasan tersebut dan itu menciptakan permasalahan identitas yang membedakan Jepang dengan Korea Utara dan juga Cina. Regionalisme semakin melemah  karena dinamika kawasan yang renggang, menegang dan fluktuatif.   Kata kunci: Regionalisme Asia Timur; Jepang; ASEAN+3; Konstruktivisme; Dilema Keamanan